PENGARUH MOTIVASI BELAJAR, INTEGRITAS INDIVIDU DAN PROKRASTINASI TERHADAP KECURANGAN AKADEMIK - Ni Kadek Pande Septia Dewi; Ni Komang Sumadi; Putu Nuniek Hutnaleontina (UNHI Press, 2022)
This research aims in this study to find out the influence of learning motivation, individual integrity and procrastination on academic fraud. The population in the study was an active undergraduate student of the Accounting Study Program of the Faculty of Business Economics and Tourism, Hindu University of Indonesia class of 2018, 2019 and ampulen students with a sample used, namely 213 respondents. The data analysis techniques used in this study are multiple linear regression, determination coefficient, t test and F test. Based on the results of the study, it can be seen that: (1) motivation to learn taxes has a negative and significant effect on academic fraud, where the regression coefficient is obtained – 0.872 and sig 0.000. (2) Individual integrity has a significant negative effect on academic fraud, where a regression coefficient of - 0.408 and sig 0.000 are obtained. (3) procrastination has a significant positive effect on academic fraud, where it obtained 0.197 regression coeffesien and sig 0.000. The magnitude of the influence of free variables on academic fraud is 54.7%. The advice that can be given by researchers is that the Hindu University of Indonesia is expected to create learning methods that can make students enthusiastic in learning.